Does adolescence anemia persist over a woman's life cycle? Evidence from the Indonesian Family Life Survey - Elan Satriawan; Ranjan Shrestha; Firman Witoelar; Takashi Yamano (Asian Development Bank (ADB), 2023)
We study the determinants of hemoglobin concentration in women throughout their life cycle and ask whether anemia during adolescence persists into adulthood. Using a panel of individuals from the Indonesian Family Life Survey (IFLS), we find that although about 30% of our sample was anemic during a given survey wave, 63% experienced anemia at least once over the four survey waves, suggesting a high burden of anemia among Indonesian women. Furthermore, the high prevalence of anemia is not limited to poor women but is also observed in the wealthier segments of the population. Using a dynamic panel framework, we find a significant relationship between current hemoglobin concentration and its measurement in the preceding survey wave, suggesting some persistence of anemia status across survey waves. However, a small autoregressive coefficient suggests that hemoglobin concentration and the likelihood of anemia converge across women over time. We find a few variables that are significant determinants of hemoglobin concentration. Among them, household socioeconomic status and wages of women compared with men in the community are positively associated with hemoglobin concentration.
Keywords: I15; I18; 330; anemia; hemoglobin concentration; Indonesian Family Life Survey; female adolescent health